2014
DOI: 10.1097/mbc.0000000000000028
|View full text |Cite
|
Sign up to set email alerts
|

Activity of thrombin-activatable fibrinolysis inhibitor in the plasma of patients with abdominal aortic aneurysm

Abstract: Patients with abdominal aortic aneurysm (AAA) experience impaired balance between fibrinolysis and coagulation, manifested by increased prothrombotic tendency and intensified inflammatory processes. The aim of this study was to evaluate the TAFI activity level (thrombin activatable fibrinolysis inhibitor) in the plasma of AAA patients. Plasma levels of PAI-1 (plasminogen activator inhibitor type 1), urokinase-type plasminogen activator and uPAR (urokinase-type plasminogen activator receptor) were measured as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Previous studies have suggested that the activities of thrombin-activatable fibrinolysis inhibitor (TAFI) and plasminogen activator inhibitor-1 (PAI-1) play crucial roles in the initiation and development of deep venous thrombus ( 11 13 ). TAFI is an anti-fibrinolytic factor, lower levels of which have been associated with certain comorbidities, such as CVD ( 14 , 15 ). However, previous studies have demonstrated that the influence of genetic variations in the TAFI gene on the risk of CVD is inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that the activities of thrombin-activatable fibrinolysis inhibitor (TAFI) and plasminogen activator inhibitor-1 (PAI-1) play crucial roles in the initiation and development of deep venous thrombus ( 11 13 ). TAFI is an anti-fibrinolytic factor, lower levels of which have been associated with certain comorbidities, such as CVD ( 14 , 15 ). However, previous studies have demonstrated that the influence of genetic variations in the TAFI gene on the risk of CVD is inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Tissue plasminogen activator (tPA) is an effective drug approved by US FDA for the treatment of ischemic stroke, and it exhibits pleiotropic effects in addition to thrombolysis (10). Thrombin-activatable fibrinolysis inhibitor (TAFI) is also an anti-fibrinolytic factor with an increased risk of cerebral infarction as the levels of plasma TAFI increase (11,12). Previous studies have suggested that TAFI and plasminogen activator inhibitor (PAI)-1serve crucial roles in the initiation and development of deep cerebral infarction (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…There are only two previous studies on TAFI in human AAA disease. In a small cohort study, Dubis et al demonstrated decreased TAFI activity in AAA patients [26]. In another study, TAFIa levels were high in patients with ruptured and non-ruptured AAA, although no control group was included [27].…”
Section: Introductionmentioning
confidence: 98%